Signaling capacity of FcγRII isoforms in B-CLL cells - Gamberale, Romina (2005)
Two main isoforms of Fcγ receptor II (CD32) have been described in humans: activatory FcγRIIA and inhibitory FcγRIIB. We have previously reported that B cells from a subset of chronic lymphocytic leukemia (B-CLL) patients express not only FcγRIIB, as normal B lymphocytes, but also the myeloid FcγRIIA. The aim of this study was to evaluate the signaling capacity of both FcγRII isoforms in B-CLL cells. We found that FcγRIIA expressed by leukemic cells failed to induce Ca2+ mobilization or protein tyrosine phosphorylation, suggesting that the receptor is not functional. By contrast, FcγRIIB effectively diminished BCR-triggered ERK1 phosphorylation, which indicates that it is able to transduce inhibitory signals in B-CLL cells. Moreover, we found that FcγRIIB homoaggregation in either B-CLL or non-malignant tonsillar B cells did not result in apoptosis as was reported for murine B splenocytes. Together, these results show that FcγRIIB, but not FcγRIIA is biologically active in B-CLL cells and might influence leukemic cell physiology in vivo. © 2005 Elsevier Ltd. All rights reserved.